MANAGEMENT OF THE HUMAN RESOURCE STRATEGY OF AN ENTERPRISE IN THE CONDITIONS OF THE MODERN BUSINESS ENVIRONMENT (Development Service Industry Management, 2025)
The article considers the main approaches to improving the enterprise's personnel strategy in the conditions of the modern business environment. It is proved that the management of the enterprise's personnel strategy plays a key role in ensuring its competitiveness and sustainable development. The article presents the main approaches to the formation of a personnel strategy, in particular, adaptation to market changes, the use of innovative methods of personnel management, the development of corporate culture and motivational mechanisms. The personnel strategy is an important tool for managing human resources at the enterprise, which ensures the effective achievement of strategic goals through the optimal use of the potential of employees. It includes a set of plans, measures and initiatives aimed at attracting, retaining and developing qualified personnel that meet the needs of the enterprise. The personnel strategy is based on a thorough analysis of internal and external factors, such as the labor market, economic situation, technological changes and others. The article presents the main stages of the formation of a personnel strategy, namely: determining the strategic goals of the organization, analyzing personnel potential, forecasting the need for personnel, developing a personnel policy, implementing personnel measures and assessing effectiveness. It also involves constant adaptation of the strategy in the face of changes in the market and within the organization. Adjusting the HR strategy is an integral part of the process, which allows you to quickly respond to internal and external challenges, such as changes in technology, legislation or organizational structure. Evaluating the effectiveness of the HR strategy allows you to identify weaknesses, improve employee motivation and increase their productivity.
Keywords: management; HR strategy; HR management; competitiveness